Interleukin-33 (IL-33) as a Diagnostic and Prognostic Factor in Traumatic Brain Injury. (10th January 2020) - Erenler, Ali Kemal; Baydin, Ahmet
Abstract : Interleukin-33 (IL-33) is a cytokine involved in interleukin-1 family. Role of IL-33 in immune system activation is well described in the literature. IL-33 has been identified as an endogenous alarm signal (alarmin) to alert various types of immune cells to trauma. In this narrative review, we aimed to underline the diagnostic and prognostic importance of IL-33 in trauma, particularly in brain trauma.